The effects of maternal voice on pain during placement of peripherally inserted central catheter in neonates - Flours, Audrey; Mons, Fabienne; Bedu, Antoine; Lauvray, Thomas; Blanquart, Anne-Laure; Woillard, Jean-Baptiste; Mowendabeka, Audrey; Guigonis, Vincent; Ponthier, Laure (Frontiers in Pain Research, 2024)
BackgroundPeripherally inserted central catheter (PICC) are a necessary procedure for preterm newborns care. Despite the use of analgesic treatments, its insertion can be painful. Our objective was to study the effect of maternal voice on pain during PICC insertion.MethodWe conducted a pre post study for 2 years. Pain was compared between the two groups (with/without maternal presence) using a neonatal pain scale (FANS). Infection rate, procedure time, number of failures, mothers’ anxiety and caregivers’anxiety were compared between the two groups.ResultsNinety neonates were eligible. Finally, 63 neonates were included. Thirty-four placements were realized without maternal voice (first period) and 29 with maternal voice (second period). Mean FANS during PICC placement was lower in the maternal voice group than in the control group (1.15 ± 1.27 vs. 1.41 ± 1.49, p = 0.033). The FANS was also lower in the maternal voice group during the time of the first cutaneous effraction (p = 0.032). There was no significant difference between the two groups concerning the other outcomes.ConclusionMaternal voice added to conventional care decreased acute pain during PICC insertion without increasing infection rate, number of failures or procedure time.